2013
DOI: 10.1055/s-0032-1333420
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Randomized, Controlled Trial Comparing Radiographic and Clinical Outcomes between Stand-Alone Lateral Interbody Lumbar Fusion with either Silicate Calcium Phosphate or rh-BMP2

Abstract: In stand-alone XLIF, SiCaP and rhBMP-2 bone graft substitutes both resulted in complete long-term fusion. rhBMP-2, however, seemed to result in more rapid early postoperative fusion, though with one instance of excessive bone formation in one patient that required subsequent surgical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(48 citation statements)
references
References 51 publications
2
46
0
Order By: Relevance
“…The potential advantages of the LLIF technique include less invasive access, the preservation of stabilizing ligaments, restoration of intervertebral disc height with indirect decompression of the intervertebral foramina, and satisfactory fusion rates (5,9,13,14). Because of the additional stabilization afforded by the LLIF procedure, the senior surgeon of this present study was encouraged to explore the impact of less extensive posterior instrumentation with the idea that unilateral pedicle screw placement may result in less operative time, less blood loss, and lower costs without compromising clinical and radiographic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The potential advantages of the LLIF technique include less invasive access, the preservation of stabilizing ligaments, restoration of intervertebral disc height with indirect decompression of the intervertebral foramina, and satisfactory fusion rates (5,9,13,14). Because of the additional stabilization afforded by the LLIF procedure, the senior surgeon of this present study was encouraged to explore the impact of less extensive posterior instrumentation with the idea that unilateral pedicle screw placement may result in less operative time, less blood loss, and lower costs without compromising clinical and radiographic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Ruetten et al [30] reported a mean VAS back of 4 (out of 100) and a VAS leg of 14 (out of 100) on postoperative day 1, stating that no post operative pain medication was required in their 463 patient series. Marchi et al [35] reported mean VAS back of 45 and VAS leg of 31 one week following surgery, while Pimenta et al [40] reported a combined VAS Back/ Leg value of 50 at the same time point. Virtually all of the data gathered involved application of the XLIF (NuVasive, San Diego, California, United States) system; there is at this point limited data on other systems.…”
Section: Dlif/xlifmentioning
confidence: 99%
“…Marchi et al [35] 2012 XLIF PCS Spondylolisthesis 52 -Sharma et al [36] 2011 XLIF RCS Spondylosis ± listhesis, scoliosis 43 -Pimenta et al [25] 2011 XLIF PCS DDD 36 -Ahmadian et al [37] 2013 XLIF RCS L4/L5 spondylolisthesis 31 -Caputo et al [38] 2012 XLIF PCS Scoliosis 30 -Malham et al [39] 2012 XLIF PCS DDD, spondylolisthesis, scoliosis 30 - 4 Pimenta et al [40] 2013 XLIF RCT L4/L5 DDD 30 -Elowitz et al [41] 2011 XLIF PCS LSS 25 -Oliveira et al [42] [27] ----28% 24% --Smith et al [28] 112 ± 31 173 ± 31 90 ± 74 311 ± 370 3% 6% 1.7 ± 1.3 3.6 ± 0.9 Rodgers et al [12] --1.4 g Hb 2.7 g Hb --1.3 5.3 Huang et al [29] 176 ± 8 202 ± 15 572 ± 93 970 ± 209 --11.6 ± 1.3 12.5 ± 1.3 Case series Rodgers et al [13] --1.38 g Hb -1% -1.2 -Ruetten et al [30] …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Silicate substituted calcium phosphate (Si-CaP) in lumbar spine and cervical spine Level I and level II studies evaluating the efficacy of Si-CaP versus autologous bone grafts are currently lacking, though two level I studies 100,101 comparing SiCaP with rhBMP were identified. Level IV retrospective studies by Jenis et al 102 and Nagineni et al 103 reported fusion rates from 76.5% to 90% with the use of Si-Cap in cervical and lumbar fusion procedures.…”
mentioning
confidence: 99%